2018
DOI: 10.1029/2018jc013824
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Offshore Export of Subantarctic Shelf Waters From the Patagonian Shelf

Abstract: It has been suggested that the Subtropical Shelf Front (STSF) could be a preferential site for the detrainment of Subantarctic Shelf Water (SASW) and related planktonic shelf species onto the open SW Atlantic Ocean. The offshore detrainment of SASW and planktonic shelf species might be an exportation mechanism, affecting the population abundances of fishing resources in Argentina, Uruguay, and Southern Brazil. In this study, we characterize for the first time the 3-D structure of the STSF and the main routes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 36 publications
5
31
0
1
Order By: Relevance
“…The other branch of SASW, the northern branch, characterized by 75% SASW concentration, continues northward over the mid-shelf, reaches 35°S (Transect 3) and 50% SASW reaches 33°S (Transect 6), near the STSF location ( Figure 5). This northernmost extent of SASW is consistent with previous observations (Möller et al, 2008;Piola et al, 2000) and numerical simulations reported by Palma et al (2008), and between the extensions found by Franco et al (2018) during summer and winter. Piola et al (2008) suggested that SASW reaches the position of the STSF, where it describes a sharp cyclonic loop and flows to the open ocean.…”
Section: Journal Of Geophysical Research: Oceanssupporting
confidence: 92%
See 3 more Smart Citations
“…The other branch of SASW, the northern branch, characterized by 75% SASW concentration, continues northward over the mid-shelf, reaches 35°S (Transect 3) and 50% SASW reaches 33°S (Transect 6), near the STSF location ( Figure 5). This northernmost extent of SASW is consistent with previous observations (Möller et al, 2008;Piola et al, 2000) and numerical simulations reported by Palma et al (2008), and between the extensions found by Franco et al (2018) during summer and winter. Piola et al (2008) suggested that SASW reaches the position of the STSF, where it describes a sharp cyclonic loop and flows to the open ocean.…”
Section: Journal Of Geophysical Research: Oceanssupporting
confidence: 92%
“…The circulation schematic is similar to those presented by Möller et al (2008) and Piola et al (2008) with the addition of the splitting SASW path near 37°S. This is in agreement with the results of Franco et al (2018) based on numerical simulations during summer. Furthermore, the double southward return path of the secondary branch of SASW onshore and offshore of the northern branch is also a new feature of the regional circulation.…”
Section: Journal Of Geophysical Research: Oceanssupporting
confidence: 89%
See 2 more Smart Citations
“…In the SWAO, the northern shelf is occupied by waters of subtropical origin and the southern shelf by waters of subantarctic origin (Piola et al, 2000). Subantarctic shelf waters are exported offshore mainly near the BMC region (Franco et al, 2018). In the northern SWAO shelf, tropical waters are observed in upper layers (Campos et al, 1995).…”
Section: Introductionmentioning
confidence: 99%